Improving the psychological well-being of prisoners through group counseling with solution-focused brief therapy (SFBT) approach - Sucipto, Ade; Purwanto, Edy; Japar, Muhammad; Iłendo-Milewska, Agnieszka (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
Psychological well-being (PWB) is important for prisoners, considering that they lead different lives and become increasingly depressed by being labeled as criminals by society. This study aims to examine the effectiveness of group counseling using a Solution-Focused Brief Therapy (SFBT) approach to improve prisoners' PWB. A quasi-experimental design was employed, with repeated measurements (pre-test, post-test, and follow-up). The subjects were 14 Class II A prisoners in Pekalongan, Indonesia, prison, with seven inmates in the experimental group and seven in the control group. They were selected using the purposive sampling technique based on inclusion criteria and low PWB levels obtained from the psychological well-being scale. The study results indicate that group counseling using the SFBT approach is effective in increasing the PWB of prisoner’s pre-test vs. post-test (MD = -64.857, SE = 3.749, p<.05), and post-test vs. follow-up (MD = -71.571, SE = 3.479, p <.05). The study findings could be used as consideration, reference, and an alternative for counselors to use the SFBT approach in dealing with problems related to psychology, especially PWB.